Shoreline analysis and erosion risk assessment of a coastal strip subjected to high anthropogenic pressure - Zambrano-Medina, Yedid; Franco-Ochoa, Cuauhtémoc; Plata-Rocha, Wenseslao; García-Páez, Fernando; Montoya-Rodríguez, Miguel; Mendoza-Baldwin, Edgar (Tecnología y ciencias del agua, 2022)
This study aims to understand the role of key drivers of historical changes in the shoreline and its implications with the erosion risk in the northern coastal strip of the state of Sinaloa, located on the east coast of the Gulf of California. Digital maps from different years (1981, 1991, 2004, and 2018) are analyzed using geographic information system software (DSAS and CERA) to examine: (a) the movement and rate of the shoreline change; and (b) the potential vulnerability consequences, and erosion risk. The obtained results indicate that between 1981 and 2018: (a) anthropogenic actions (dams and breakwaters) were the main drivers of both the shoreline changes and the environmental damage underlying the erosion risk that has occurred in recent decades; (b) the coastline of the study area has been eroding with an average EPR of -3.1 m per year, which has led to an average NSM of -112.9 m; and (c) the risk of erosion remained moderate, although the vulnerability increased from a moderate to a high level and potential consequences from a very low to a moderate level. Besides, the results of this study provide a basis for future analyses focused on predicting shoreline changes and coastal risk.